DETECTIVE PATTERNS IN THE PALE BLUE EYES (2022) FILM - Sulistyani, Syabrina Sri; Bella Siti Nur Azizah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This study explores the application of John G. Cawelti's classic detective formula in the film The Pale Blue Eye (2022), which is an adaptation of Louis Bayard's 2003 novel. As part of popular literature, the film represents the enduring appeal of the mystery-detective genre through recognizable narrative patterns and conventions. Using a qualitative descriptive approach and narrative analysis techniques, this study identifies how the six main elements of the classic detective formula (1) mysterious crime situation, (2) introduction of the detective character, (3) investigation process, (4) announcement of the solution, (5) explanation of the solution, and (6) final resolution, are implemented in the film's story structure. The results of the analysis show that the film not only follows the conventional structure of the detective genre, but also enriches the narrative through additional elements such as a Watsonian-style narrator (Edgar Allan Poe) and the existence of a two-layer solution that deviates from the role of the classic detective as a neutral and detached figure. Thus, The Pale Blue Eye proves the flexibility and cultural relevance of the detective story formula in contemporary popular media, as Cawelti's theory suggests that genre conventions serve as both structural guides and mirrors of cultural meanings.